Удосконалення механізму економічної мотивації як стратегічний імператив управління персоналом промислового підприємства - Жовновач, Р. І.; Малаховський, Ю. В.; Жовновач, Р. И.; Малаховский, Ю. В.; Zhovnovach, R.; Malakhovskyi, Yu. (ЦНТУ, 2019)
Статтю присвячено проблемі розвитку методологічних засад формування та удосконалення механізму економічної мотивації. Розкрито понятійно-термінологічний апарат дослідження. Узагальнено теоретичні засади, з’ясовано сутність, економічну природу механізму мотивації працівника як стратегічного імперативу управління персоналом промислового підприємства. Структуровано інструменти економічної мотивації у забезпеченні ефективної праці і постійного професійного розвитку персоналу. Запропоновано шляхи удосконалення механізму економічної мотивації на основі побудови системи матеріального стимулювання на промисловому підприємстві як складової процесу бюджетування виробничої і фінансової діяльності. Статья посвящена проблеме развития методологических основ формирования и совершенствования механизма экономической мотивации. Раскрыт понятийно-терминологический аппарат исследования. Обобщены теоретические основы, раскрыта сущность, экономическая природа механизма мотивации работника как стратегического императива управления персоналом промышленного предприятия. Структурированы инструменты экономической мотивации в обеспечении эффективной работы и постоянного профессионального развития персонала. Предложено усовершенствование механизма экономической мотивации на основе построения системы материального стимулирования на промышленном предприятии как составляющей процесса бюджетирования производственной и финансовой деятельности. The article is devoted to solving the problem of development of methodological foundations of the formation and improvement of the mechanism of economic motivation as a strategic imperative of personnel management at an industrial enterprise. The conceptual and terminological apparatus of the research has been formed. Particularly, the author's point of view on the meaning of the concepts “imperative”, “strategic imperative”, “strategic imperatives of personnel management”, “economic motivation” is presented. The author’s definition of the essence of strategic imperatives of personnel management as a set of policies, programmes and specific actions for the formation and development of productive capabilities of employees, as well as mechanisms for their effective use in the long term was suggested. The mechanisms are focused on the achievement of strategic goals of enterprise development taking into account its resource potential. The theoretical foundations have been summarized. The essence and economic nature of the mechanism of employee’s motivation as a strategic imperative for personnel management at an industrial enterprise were clarified. It is noted that the main motivating factor of the employees is to get guaranteed wages and to meet other primary material needs. Structuring the set of tools of economic motivation to ensure efficient work and continuous professional development of staff creates additional opportunities for a deeper understanding of the impact of motivation methods on the activity of company staff in order to enhance its innovative component in the strategic perspective and the level of efficiency of work with the methods of economic impact. The strategic directions of improvement of the mechanism of economic motivation on the basis of creating the system of material incentives at an industrial enterprise as a component of the process of production budgeting and financial activity have been offered. Increasing the effectiveness of the mechanism of economic motivation on the basis of budgeting is ensured through the measures connected with the use of the budget indicators of the responsibility centers at the enterprise as the basis of bonuses. The increase in the effectiveness of the mechanism also takes into account the influence of certain divisions of the enterprise as centers of responsibility for determining the value of the bonus fund. It necessary to determine the conditions, indicators and rates of remuneration for certain divisions and employees of the enterprise, including those related to the formation of innovation portfolio and innovation policy.
Совершенствование механизма экономической мотивации как стратегический императив управления персоналом промышленного предприятия
Improvement of the Mechanism of Economic Motivation as a Strategic Imperative of Personnel Management at an Industrial Enterprise
Keywords: управління персоналом; мотивація; економічна мотивація; стратегічний імператив; матеріальне стимулювання; заробітна плата; преміальний фонд; бюджетування; центри фінансової відповідальності; промислове підприємство; управления персоналом; мотивация; экономическая мотивация; стратегический императив; материальное стимулирование; заработная плата; премиальный фонд; бюджетирования; центры финансовой ответственности; промышленное предприятие; personnel management; motivation; economic motivation; strategic imperative; material incentives; wage; bonus fund; budgeting; centers of financial responsibility; industrial enterprise